Financial performance for the period of 2004-2010 of ten selected high revenue private level 4 hospitals in Metro Manila, which were the subject of investor interest, and which were identified as leading players in medical tourism. - Santos, Roselmo Z. Doval
There is considerable investment interest in the healthcare industry with the government prioritization of Private Public Partnership for Health as well as the establishment of PEZA and TIEZA incentives for medical tourism. However, there is insufficient research on financial performance indicators for the Philippine hospital industry. The present study did a financial ratio analysis of ten top performer hospitals engaged in Medical Tourism from 2004-2010. It seeks to complement the study of De la Pena, et al (Dela Pena, Lawas, Sison, 2005) which looked at the financial performance of Philippine hospitals from up to 2003.